Development of molecular imprinted biosorbent by using orange peel for Pb2+ removal from aqueous solution - Syaimaa Rosman, Andrew (2010)
In this research,the investigation of the use of orange peel which has high adsorption capacity of heavy metals compare to other types of biosorbent were carried out.In order to determine the most effective adsorption for each of heavy metals,we had come out in development of molecular-imprinted technology.Molecular-imprinted technique tends to give a higher adsorption rates and higher selectivity towards target metals.In order to achieve the objectives of this research,it would based on four main scopes of study which is to know effect of imprinting ions concentration on biosorption,effect of time on biosorption,effect of initial concentration of Pb2+ in solution and also to compare the different type of metals on adsorption selectivity of the biosorbent.The adsorption uptake was analyzed by using Atomic Absorption Spectrophotometer AAS).In the preparation, with the imprinted ion Pb 2+ concentrations increasing,the more fucntional groups(-OH)were protected and the more imprinting sites on the surface were retained.So,the loading amount of imprinted ions in preparation was 2 mg/g selected as the optimum loading amount.For the effect of time in adsorption,the optimum condition was described as the shortest time that the biosorbent can absorbed the metals. So,in this experiment,the shortest time that it can achieved with a high adsorption capacity was 30 minutes.It can be said as satisfactory adsorption compare to without imprinted biosorbent.The existence of functional group of (-OH) can be proved by using FTIR analysis.It was recommended that this research was furthered by using wastewater from metal industry,to recover back the Plumbum that had attached to the biosorbent,and can be applied in adsorption column.